Huertos energéticos versus huertos alimentaríos en el uso del suelo en el Ecuador. aspectos técnicos y económicos - Chóez Mejía, Diana Mariel (2010)
The next issue of graduation project is done analyzing geographic and territorial wealth held by Ecuador to provide a source of renewable energy with environmental sustainability and aimed to break down barriers so dear black gold (oil) primarily responsible for contamination of our ecosystem, the main goal as a group was to create an additive-based vegetable oil extraction which raw material are the seeds of the gear to be mixed with petroleum diesel, this plant is bushy oilseed an oil yield of 2.5 tons / ha, our process starts from the crop, then you get your machine oil through a Brazilian origin with a yield of 368 liters / day, ultimately resulting in the additive after the refining stage. This project received final result a NPV of $ 392,792.11, and an IRR of 14.90%, demonstrating that the project is economically viable and it is feasible from the environmental point of view and with improvements to the diesel engine in its application as an additive for fuel